On the Characteristics of Misaligned Journal Bearings - Joon Young Jang (Lubricants, 2015)
Journal bearing misalignment arise generally from the shaft deformation under load, deflection of the shaft, manufacturing and assembly errors, improper installation, and asymmetric loading. During operations, misalignment has a considerable effect on the static and dynamic performances. It could cause wear, vibration and even system failure. In this article, a literature review of misalignment of the journal bearings is presented. The basic theory for the misalignment and some results for the circular journal bearing are also presented to show the general trends of the misalignment.